Association of Glutathione–S-Transferase (GSTP1) Genetic Polymorphism in Iraqi Patients with Diabetes Mellitus Type2 (Baghdad Science Journal, 2016)
Glutathione S-transferases (GSTs) are enzymes that included, in a more range of detoxifying reactions by conjugation of glutathione, to electrophilic material. Polymorphisms n the genes that responsible of GSTs affect, the function of the GSTs. GSTs play an active role in protection of cell against oxidative stress mechanism. Polymorphisms of GSTP1 at codon 105 amino acids forms GSTP1 important site for bind of hydrophobic electrophiles and the substitution of Ile/Val affect substrate specially catalytic activity of the enzyme and may correlate with reach to different diseases in human like diabetes mellitus type2 disease. Correlation between these polymorphisms and changes in the parameters file of diabetic patients has also been found, therefore, the results variation considerably among the studies; therefore, these control study was designed to leading to detecting know, as there are no studies on this performed in the people of Iraq. The polymerase chain reaction-restriction fragment length polymorphism was used to study GSTP1genetic polymorphism in 60 T2DM patients and 50 healthy individuals. Our results showed that presence of the GSTP1 heterozygous mutant allele Ile/Val was more common in subjects with T2DM than in the control group (40.00% and 32.00%, respectively; p = 0.01), as well as the found of the homozygous mutant of GSTP1 allele Val/Val was common in T2DM patient and not found in the control group (3.33% and 0.00%, respectively; p = 0.001).GSTP1 genotypes do not have an effect on blood lipids after infection with diabetes mellitus. Agarose gels used to determined genotypes according to the bands were that appeared in electrophoresis of gel.